The Mediating Role of Brand Equity in the Relationship Between Perceived Quality and Consumer Loyalty - Adelia Rizki Pradita; Salman Faris Insani; Yoppi Syahrial (P3I UMSurabaya, 2024)
This study aims to examine the impact of perceived quality on consumer loyalty, with brand equity serving as a mediating variable among Samsung smartphone users in Indonesia. The sample comprised 137 respondents, obtained through purposive convenience sampling. The analysis technique is Structured Equation Modeling (SEM) conducted using the IBM SPSS AMOS 24 application program. The findings reveal that while perceived quality does not have a direct impact on consumer loyalty, it does have a significant positive effect on brand equity, which in turn has a positive and significant impact on consumer loyalty. Brand equity has a positive and significant impact on consumer loyalty. In addition, brand equity mediates the effect of perceived quality on consumer loyalty fully. Therefore, brand equity plays a mediating role in consumer loyalty.